Uncertainty and precaution in hunting wolves twice in a year: Reanalysis of Treves and Louchouarn: Reply to Stauffer et al. - Adrian Treves (PLoS ONE, 2025)
Stauffer et al. (2024) present an alternative approach to modeling a one-year change in the wolf population of the state of Wisconsin, USA. They found an error in the code in Treves & Louchouarn 2022, which we corrected. It did not change that paper’s conclusions. However, Stauffer et al. accept the state of Wisconsin’s estimate for wolf abundance in 2022, which is based on undescribed methods, unshared data, lacks peer review, and depends on a method we have criticized for imprecision, inaccuracy, insensitivity to changing conditions, and irreproducibility. An occupancy model constructed and validated for a period several years after legal wolf-killing is a dubious basis for estimating wolf abundance one year after unprecedented, legal wolf-killing. Finally, undisclosed data continue to mar the work of state-funded scientists.